Laryngeal morbidity after intubation with or without neuromuscular block in thyroid surgery using recurrent laryngeal nerve monitoring - Birkholz, Torsten; Irouschek, Andrea; Saalfrank-Schardt, Christina; Klein, Peter; Schmidt, Joachim (Auris Nasus Larynx, 2012)
The avoidance of neuromuscular blocking agents (NMBA) for endotracheal intubation is associated with a higher incidence of laryngeal discomfort and lesions, but could impair effectiveness of intra operative recurrent laryngeal nerve monitoring (IONM).In a retrospective quality assessment study over a period of 30 months, a collective that had been intubated without NMBA was compared with a group, which had received NMBA. Endolaryngeal EMG was accomplished with a MagStim(®)-EMG-electrode.Out of the 127 patients with 224 nerves at risk (NAR; NMBA 102 NAR, no NMBA 122 NAR), more than 90% received a total intravenous anaesthesia with propofol, and 88% had remifentanil. Laryngeal side effects and damage scores did not differ significantly.In this special setting of IONM and thyroid surgery, avoidance of NMBA for endotracheal intubation seems not to increase the incidence of laryngeal side effects and lesions. If endotracheal intubation without NMBA is required, the authors suggest a standardized approach using induction agents as propofol and remifentanil.
EVALuna2:15058